URGENSI KAJI ULANG REGULASI ANTI SLAPP TERHADAP PEJUANG KEADILAN LINGKUNGAN HIDUP - Paka, Arsafina; Najicha, Fatma Ulfatun (Universitas Wiralodra, 2023)
The polemic of environmental problems create an Anti-Strategic Lawsuit Against Public Participations (Anti-SLAPP) concept, as a solution to overcome the problem of removing public participation in the fight for environmental justice that has been regulated in Article 66 of Law Number 32 Year 2009 concerning The Protection and Management of The Environment. But in fact, that regulation doesn't guarantee legal protection and justice for all of the people, especially for the environmental activists. The issuance of Law Number 11 Year 2020 which changes the main elements related to the environment, provides an in-depth analysis space for author. Based on that, the purpose of this paper is to analyze the relevance of the Anti-SLAPP regulation and its implementation in realizing environmental justice, and the mechanism for strengthening the Anti-SLAPP regulation related to the issuance of Law Number 11 Year 2020. The method used in this paper is a juridicalnormative method with secondary data that were collected through literature study and journals. The result of the research and study is the Anti-SLAPP regulation in Law Number 32 Year 2009 concerning The Protection and Management of The Environment, as changed in Law Number 11 Year 2020 is inconsistent with the fact. Therefore, this problem requires improvements in terms of legal substance, structure, and culture in order to realize a comprehensive environmental justice. Keywords : “Anti-SLAPP”, “Environmental justice”, “Strengthening regulation”.